Optofluidic Particle Manipulation: Optical Trapping in a Thin-Membrane Microchannel - Zachary J. Walker; Tanner Wells; Ethan Belliston; Seth B. Walker; Carson Zeller; Mohammad Julker Neyen Sampad; S. M. Saiduzzaman; Holger Schmidt; Aaron R. Hawkins (Biosensors, 2022)
We demonstrate an optofluidic device which utilizes the optical scattering and gradient forces for particle trapping in microchannels featuring 300 nm thick membranes. On-chip waveguides are used to direct light into microfluidic trapping channels. Radiation pressure is used to push particles into a protrusion cavity, isolating the particles from liquid flow. Two different designs are presented: the first exclusively uses the optical scattering force for particle manipulation, and the second uses both scattering and gradient forces. Trapping performance is modeled for both cases. The first design, referred to as the orthogonal force design, is shown to have a 80% capture efficiency under typical operating conditions. The second design, referred to as the gradient force design, is shown to have 98% efficiency under the same conditions.